الاستثمار في القيم المنقولة كوسيلة لتمويل الشركات - عيشوش, مبروكة (جامعة الوادي -University eloued, 2017)
من خلال دراستنا لموضوع الاستثمار في القيم المنقولة , يتضح أن التشريع الجزائري اهتم بهذا النوع من مصادر التمويل وذلك بسن عدة قوانين خاصة بتداول القيم المنقولة أو ما يعرف بالأوراق التجارية ,ويعتبر المرسوم التشريعي رقم 93/10المعدل والمتمم المتعلق ببورصة القيم المنقولة حجر الأساس للسوق المالية الجزائرية . تعد كل من الأسهم والسندات أهم القيم المنقولة فالأسهم سند ملكية و السندات سند مديونية ويتم اللجوء إلى أحدهما حسب الظروف الاقتصادية كمستوى التضخم وسعر الفائدة الناتج من استثمار هذه الأوراق . تعد البيئة الاستثمارية من أهم العوامل المؤثرة في استثمار القيم المنقولة وقد حرص التشريع الجزائري على توفير بعض الضمانات التي من شانها تشجيع هذا النوع من الاستثمارات كرس هذه الضمانات في نصوص عدة هذه الأخيرة والتي من خلالها يقدم المستثمر أو المدخر على استثمار أمواله دون خوف من المخاطر المحيطة به .Through our study of the subject of investing in movable values, it is clear that Algerian legislation is concerned With the enactment of several laws concerning the circulation of movable values or what is known as commercial papers. Legislative Decree No. 93/10, which is amended and supplemented with the Stock Exchange, is the cornerstone of the Algerian financial market. Both stocks and bonds are the most important movable values. Shares are bonds of title and bonds, and one is used according to the economic conditions such as the level of inflation and the interest rate resulting from the investment of these securities. The investment environment is one of the most important factors influencing the investment of movable values. The Algerian legislation is keen to provide some guarantees that would encourage this type of investment. These guarantees were enshrined in several provisions of the latter, whereby the investor or saver saves money without fear of surrounding risks with it .
ماستر اعمال
Keywords: القيم المنقولة- مصادر التمويل- بتداول- ببورصة- الأسهم- والسندات- الضمانات- الاستثمارات- المخاطر-شفافية- وعلانية- مستقلة.; Moved Assets - Sources of Finance - Trading - Stock Exchange - Bonds - Guarantees - Investments - Risks - Transparency - Public - Independent.